Supramalleolar Osteotomy Combined With an Intra-articular Osteotomy for the Reconstruction of Malunited Medial Impacted Ankle Fractures. (December 2018) - Guo, Changjun; Liu, Zongbao; Xu, Yangbo; Li, Xingchen; Zhu, Yuan; Xu, Xiangyang
Background: Malunion of a medial impacted ankle fracture may cause varus ankle deformity. This retrospective study examined the use of supramalleolar osteotomy combined with an intra-articular osteotomy in patients with malunited medial impacted ankle fractures. Methods: Twenty-four patients with malunited medial impacted ankle fracture were treated between January 2011 and December 2014. Using Weber's classification, 10 had type A fractures and 14 had type B, and with the AO classification, 20 had 44A2 and 4 had 44B3. All of these patients had varus ankle deformity. Supramalleolar osteotomy combined with an intra-articular osteotomy was performed. The visual analog scale (VAS) for pain during daily activities, the Olerud and Molander Scale and the modified Takakura classification stage were used to determine the clinical outcomes and a radiographic analysis was performed. Results: The radiographic parameters, including the tibial ankle surface (TAS) angle and talar tilt angle (TTA), showed significant differences between the preoperative and follow-up assessments. The mean tibial lateral surface (TLS) did not show a significant change. The average Olerud and Molander Scale score improved significantly from 56.4 ± 6.21 preoperatively to 77.0 ± 6.11 at the latest follow-up ( P < .01). The mean VAS decreased significantly from 6.7 ± 0.8 preoperatively to 3.1 ± 0.6 at the latest follow-up ( P < .01). No significant difference in the modified Takakura classification stage was observed between the preoperative assessment and the last follow-up. Conclusions: The use of a supramalleolar osteotomy combined with an intra-articular osteotomy was an effective option for the treatment of malunited medial impacted ankle fractures associated with varus ankle deformity. Level of Evidence: Level IV, retrospective case series.